Influence of the ITZ Thickness on the Damage Performance of Recycled Concrete - Fuwei Xu; Bin Tian; Gang Xu (Advances in Materials Science and Engineering)
The interfacial transition zone (ITZ) is a weak region of recycled concrete. To further study the influence of the ITZ on the damage performance of recycled concrete, a formula for calculating the ITZ thickness is derived, and the ITZ thickness is calculated for various recycled concrete mixtures with a recycled aggregate content of 30%. The concrete model test method and finite element analysis software were used to numerically simulate common concrete and recycled concrete with ITZ thicknesses of 0.05 mm, 1 mm, 2 mm, 3 mm, and 4 mm. The results show that the thickness of the ITZ has an obvious influence on the cracking strength of recycled concrete and that the cracking strength of recycled concrete decreases with increasing ITZ thickness. The cracks in recycled concrete initiate from the ITZ, and the damage degree increases with increasing ITZ thickness. Compared with that of common concrete, the cracking strength of recycled concrete with an ITZ thickness of no more than 2 mm (i.e., the replacement rate of the recycled aggregates is no more than 30%) is not significantly reduced.